Predictors of long term tricuspid regurgitation after pulmonary valve replacement: a single center study on the cohort of significant preoperative tricuspid regurgitation. (3rd October 2022) - Carbonell Prat, B; Dos, L; Gordon, B; Ligero, C; Gonzalez, V; Vilte, G; Pijuan, A; Miranda, B; Ferre, M; Lorente, M; Guedes, P; Ferreira, I; et al.
Abstract: Background: Almost one-third of repaired tetralogy of Fallot (TOF) and pulmonary stenosis (PS) patients referred for pulmonary valve replacement (PVR) have at least moderate tricuspid regurgitation (TR). Predictors of long term TR in this population are not well defined and the role of Tricuspid Annuloplasty (TA) in addition to PVR in this setting is controversial. Purpose: Patients with preoperative severe TR or moderate TR with dilated tricuspid annulus (>40mm) undergo TA at the time of PVR as per protocol in our instititution. The aim of this observational study was to evaluate the long term results of this approach and to identify predictors of significant TR at the end of follow-up. Material and methods: We retrospectively reviewed 35 repaired TOF and PS patients who underwent surgical PVR with (n=17, group 1) or without (n=18, group 2) TA in a single tertiary hospital between June-2009 and June-2021. Pre- and postoperative echocardiographic and cardiac magnetic resonance data were assessed for TR severity and right ventricle size and systolic function. Baseline and clinical follow up data were collected. Uni- and multivariable tests were used to analyze predictors of at least moderate TR after PVR. Results: Mean age at PVR and baseline image parameters were comparable between groups, except for TR grade (p 0.006), tricuspid annulus size (p 0.018) and right ventricle outflow tract diameter (p 0.04) which were greater in group 1. TA did not confer and increased risk of surgical and peroperative complications. Intensive care unit (p 0.94) and total hospital admission days (p 0.59) did not differ among groups. At one year, TR grade significantly improved regardless of TA. At the end of follow-up (5.29±2.9 years), the degree of TR increased in both groups with no differences between groups (p 0.38) (see table 1). In univariable analysis, two independent predictors of at least moderate TR at end of follow-up were identified; mixed TR mechanism (OR 12.5, p 0.006) and severe preoperative TR grade (OR 10.21, p 0.003). Mixed TR mechanism (OR 15.78, p 0.01) and a right ventricle ejection fraction below 45% (OR 1.47, p 0.01) were identified as risk factors of significant TR in multivariable analysis (see Table 2). Conclusions: TA seems a reasonable approach at the time of PVR in patients with severe TR or moderate TR with dilated annulus. Mixed TR mechanism and a worse right ventricular function have been identified as independent predictors factors of long term significant postoperative TR in our study cohort. Funding Acknowledgement: Type of funding sources: None.